Use of miniaturized tensile specimens to evaluate the ductility and formability of dual phased steels for Rapid Alloy Prototyping - Lintao Zhang (Materials Science and Engineering: A, 2023)
This work aims to investigate feasibility of using non-standard miniaturized tensile specimens (MTS) to characterise total elongation and formability behaviour of dual phase steels: to establish the scaling rules for MTS to predict a range of mechanical properties of steels obtained through rapid alloy prototyping (RAP) in the laboratory. Accurate measurement of these properties using miniature specimens allows the formability behaviour of materials produced using RAP, a process which can produce lab scale samples of 100 grams. This allows the effects of multiple compositions and thermomechanical processing parameters on formability to be evaluated. For this study, the ability of miniature tensile specimens to characterise ductility, forming limits and r-values has been compared to properties measured using standard sized tensile specimens for the dual phase steels, DP600 and DP800. 5 different tensile specimens were investigated, with gauge lengths varying from 80 mm to 5 mm and samples were taken at different orientations to the rolling direction. Total elongation was evaluated against slimness ratio for each tensile sample using the Bertelle-Oliver method and good correlations were obtained, despite specimen thicknesses being below the critical value, and the tensile strength of DP800 exceeding the limit stated for the method. Forming limit curves (FLC) were predicted using the Keeler-Brazier method, based on tensile data obtained using the standard and non-standard tensile specimens These curves compared favourably to experimentally obtained FLCs, however the curve predicted using the miniaturised tensile specimen over-predicted the major strain. The anisotropy of the rolled sheet steels was characterised from r-values obtained from tensile tests performed at different orientations to the rolling direction. Values obtained from the miniature tensile test were comparable to those obtained from standard tests within the range of scatter. The results obtained through this study provide confidence in using the miniature tensile specimens to predict the formability of heterogeneous alloys such as DP steels, manufactured using the RAP process.